Market chain analysis of poultry: the case of Alamata and Atsbi-womberta Woredas of Tigray - Gebregziabher, D. (Haramaya University, 2010)
This study was initiated to analyze poultry marketing chain in Alamata and Atsbi-Wonberta Woredas of Tigray region. The specific objectives of the study are, to analyze structure conduct and performance of poultry market, to analyze the structure of production cost and determine profitability, to identify the major constraints and opportunities of poultry production and supply, to analyze the production and marketing support service of extension, input supply, credit and marketing, and to identify the determinants of poultry supply in the study areas. The data were collected from individual interview using pre-tested questionnaire. Descriptive statistics such as t-test, chi-square, means and percentages were employed to analyze structure conduct and performance of poultry market, to analyze the structure of production cost and determine profitability, to identify the major constraints and opportunities of poultry production and supply and to analyze production and marketing support service of extension, input supply, credit and marketing. Heckman two stage econometric model was used to identify factors affecting market participation decision and value of poultry sales. The major marketing channels and main actors involving in the market were identified. Marketing channels of egg and chicken indicated shorter path as compared to other agricultural commodities. The market actors in the survey period were producers, rural assemblers, retailers, wholesalers and consumers. Significant amount of chicken and egg were channeled through the first channel, direct selling of the commodities from farmers to consumers. To evaluate poultry market performance cost, profit and marketing margins were calculated for the group of market players in different channels for egg and chicken markets. xiv Poultry production was constrained by diseases, health service and limited supply of exotic chicken. Some of the diseases identified by the sample households were New Castle, Salmonella and chicken flies. Traders were also constrained with permanent market place, trade license and existence diseases. Despite this, it had also opportunities such as high turnover earning, small feed requirement, lower initial cost requirement, employment opportunities for poor women, landless farmers and disadvantaged groups and being land a less limiting factor for its production. Results obtained from the first stage of the model indicated that sex of the household and distance to the woreda market; family size and education of the household head were the variables that influence the decision to participate in poultry market negatively. Results from second stage of the model shows that, value of poultry sales was influenced negatively by Alamata as compare to Atsbi woreda, and positively by poultry owned. Therefore, policy aimed to accelerate agricultural development in poultry production and marketing could be successful if the aforementioned factors are taken in to consideration.